THE EFFORTS TO INCREASE STUDENTS MATHEMATICAL COMMUNICATION SKILL TROUGH THE USE OF POWERPOINT AND GUIDED DISCOVERY METHODOLOGYON THE STUDY OF CURVED-FACE-THREE-DIMENSIONAL OBJECT (STUDY CASE ON CLASS IX B MTsN CIMAHI – WEST JAVA, INDONESIA) - Sylvia Rahmi; Rifka Nadia; Rubiatur Rubiatur; Bibih Hasibah (Kopertis Region IV Jabar and Banten, 2018)
The background of this research is due to the low ability of students' mathematical communication in class IX B MTs Negeri Kota Cimahi. The purpose of this study to determine how the implementation of mathematics learning using power point and to determine the improvement of students' mathematical communication skills on the Curved-face-theree-dimensional object after applying the method of guided discovery. The research method used is Classroom Action Research (PTK) with 3 cycles that are packaged in Lesson Study program. Data collection techniques used documentation, observation, and tests. The result of the research shows that the implementation of mathematics learning using power point with guided discovery method runs conductively and shows positive response, and there is improvement of mathematical communication ability on the 3rd cycle. This is proven by tackling the students' formative value seen from the absorptive power of classical cycle 1 65.39% to 72.94% in cycle 2 and to 86.59% in cycle 3. Based on the results obtained is expected that educators can apply powerpoint spinning with good planning and implementation so that the ability of students' mathematical communication can increaseKeywords: PTK, Lesson Study, Guided Discovery, Mathematical Communication, Power Point